An extended model of Theory of Planned Behavior to investigate highly-educated iranian consumers' intentions towards consuming genetically modified foods. (1st August 2019) - Akbari, Morteza; Fozouni Ardekani, Zahra; Pino, Giovanni; Maleksaeidi, Hamideh
Abstract: The diffusion of genetically modified (GM) foods is still a controversial topic in the world's scientific and political communities and, in developing countries, where individuals may have different levels of knowledge about GM foods, consumers' attitude and intention toward these products is still under-researched. To address this gap, this study investigated the predictors of GM foods consumption intention among a random sample of 372 highly-educated Iranian consumers using a modified version of the Theory of Planned Behavior. For this purpose, corporate social responsibility, trust in and concerns about GM foods and the Regulatory Focus Theory promotion and prevention dimensions were integrated into the Theory of Planned Behavior. Structural equation modeling was used to test the theoretical model based on the field data. Results revealed that attitude, trust in GM foods, and concerns about the health and environmental impacts of GM foods predicted the intention to consume such products. In addition, consumers' perception of GM foods producers' adherence to corporate social responsibility predicted the intention to consume these products. These findings add new insights to the research on the predictors of GM foods consumption. Furthermore, the obtained results provide policymakers and producers with suggestions about highly-educated consumers' attitudes and intentions towards GM foods and may help them make effective decisions about producing, importing and placing GM foods on the market. The results appear particularly important for developing countries where there is little knowledge about GM foods and there is disagreement among policy makers, scientist and planners about the health and environmental impacts of these products. Highlights: Consumers' intention to consume genetically modified (GM) foods was investigated. The study assessed a mixed modeling approach toward predictive factors of intention. A survey was conducted with 372 Iranian consumers. Intention can be affected by attitude, trust, concerns, and Corporate Social Responsibility (CSR). The mixed model predicted 64% of variance changes in consumers' intention.